OR17-05 Hypospadias Is a Predictor of Adverse Cardiometabolic Risk in Adulthood - a Case-Control Study - Lucas-Herald, Angela K (J Endocr Soc, 2020)
Introduction: Abnormal development of the genital tract during the first trimester can lead to hypospadias. This stage coincides with the programming window during which androgens are required for normal masculinisation of the genital tract. Since fetal development may also be associated with long-term effects on cardiometabolic outcome and testosterone is itself an important vascular hormone, we questioned whether adults with a history of hypospadias are at increased risk of long-term cardiovascular and metabolic disease. Aim: This retrospective study determined if hypospadias is associated with increased risk of cardiometabolic disease later in life. Methods: Cardiovascular and diabetes admissions data were extracted through record linkage for all males with a history of hypospadias (ICD10 Q54) from 1981 to 2019 through the NHS Scotland Information Services Division after ethics approval. Controls were matched for age, birthweight, gestation and deprivation index. Incident admissions for angina, arrhythmia, diabetes, heart failure, ischaemic heart disease, myocardial infarction, peripheral arterial disease, renal failure and stroke were obtained for each individual. Case control analysis was performed using Chi square test using R. Results: Admission data on 13,481 men with hypospadias and 9,615 matched controls were reviewed. Men with hypospadias had a 10- fold higher risk of diabetes (9.7 [8.4-11.2], p<0.0001); 9- fold higher risk of ischaemic heart disease (OR [95% CI] 9.1[8.1-10.2], p<0.0001); 8- fold higher risk of renal failure (7.9 [6.9-9.1], p<0.0001); 6- fold higher risk of stroke (6.2 [5.2-7.2], p<0.0001); 6- fold higher risk of myocardial infarction (6.4 [5.6-7.3], p<0.0001); 6-fold higher risk of angina (5.9 [5.3;6.8], p<0.0001); 5-fold higher risk of arrhythmia (4.8 [4.2-5.4], p<0.0001) 5- fold higher risk of peripheral arterial disease (4.8 [3.7-6.1], p<0.0001) and 4- fold higher risk of heart failure (3.6 [3.1-4.1], p<0.0001). Conclusions: Men with a history of hypospadias are at significantly increased risk of admission for treatment for cardiovascular and metabolic conditions, especially ischaemic heart disease, diabetes and renal failure. The mechanisms underlying this observed increase are unclear and merit further evaluation.